Screen Time and its Relation with Ophthalmic Problems among Medical Students - Nadia Nisar, Roma Salman, Sameen Farooq, Sharjeel-Ur-Rehman, Ambreen Javed, Aiman Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The inflated use of digital screens has completely changed the lives of people physically, mentally and psychologically. The covid-19 pandemic has also compelled people of all age groups to shift to digital media. The average screen time usage is 7-9 hours a day which is alarming. Aim: To find out the relation of screen time with ophthalmic problems among medical students. Study Design: Cross-sectional study Place and Duration of Study: Department of Community Medicine, HITEC-IMS Taxila from 1st January 2020 to 30th June 2020. Methodology: One hundred and fifty two medical students were included using non probability convenience sampling technique. An electronic questionnaire was developed and Google forms were used for data registration. Results: The relation between screen time duration with difficulty in refocusing (p=0.05) and eye redness (p=0.05). No relation was found between screen duration and headache, eye strain, blurred vision and refractive errors. Conclusion: High screen time is found to be related to ophthalmic problems like difficulty refocussing and eye redness which if not addressed properly might result in detrimental effects. Keywords: Ophthalmic problems, Screen time, Digital devices